2009
DOI: 10.1158/0008-5472.can-09-0884
|View full text |Cite
|
Sign up to set email alerts
|

Functional Phosphodiesterase 11A Mutations May Modify the Risk of Familial and Bilateral Testicular Germ Cell Tumors

Abstract: Inactivating germline mutations in phosphodiesterase 11A (PDE11A) have been implicated in adrenal tumor susceptibility. PDE11A is highly expressed in endocrine steroidogenic tissues, especially the testis, and mice with inactivated Pde11a exhibit male infertility, a known testicular germ cell tumor (TGCT) risk factor. We sequenced the PDE11A gene-coding region in 95 patients with TGCT from 64 unrelated kindreds. We identified 8 nonsynonymous substitutions in 20 patients from 15 families: four (R52T, F258Y, G29… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 20 publications
7
73
2
1
Order By: Relevance
“…Moreover, we found three other sequence variants, i.e. R804H, R867G, and M878V, associated with a reduced PDE activity in vitro, further suggesting that these variants, also present in the general population, could contribute to a genetic predisposition to endocrine lesions (10)(11)(12). Contrary to what has been reported in adrenal and testicular tumors, we did not detect any nonsynonymous substitutions in GAF A and GAF B, the cGMP binding domain of the enzyme.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Moreover, we found three other sequence variants, i.e. R804H, R867G, and M878V, associated with a reduced PDE activity in vitro, further suggesting that these variants, also present in the general population, could contribute to a genetic predisposition to endocrine lesions (10)(11)(12). Contrary to what has been reported in adrenal and testicular tumors, we did not detect any nonsynonymous substitutions in GAF A and GAF B, the cGMP binding domain of the enzyme.…”
Section: Discussioncontrasting
confidence: 69%
“…The most frequent missense variation found in acromegalic patients and in controls was the Y272C substitution, a relatively frequent polymorphism listed in the databases. Although frequent in the general population, it has been recently reported that when transfected in murine Leydig tumor cell line 1, this variant was associated with higher cAMP levels and lower PDE activity in comparison with the wild-type enzyme (12). Moreover, we found three other sequence variants, i.e.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations